Desain Rak Penyimpanan Berkas Rekam Medis di Rumah Sakit Universitas Airlangga Surabaya - Day Rahmania; Andri Permana Wicaksono; Novita Nuraini (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Filling room has an important role in maintaining medical records, especially in terms of storage and protection of medical records. The creation of officers ease in taking and storing medical records in supported by the existence of an ergonomic storage space that is adapted to the anthropometric aspects. The design of the storage rack in accordance with the anthropometric data of the officer can facilitate the work of the officers. Storage racks at Airlangga University Hospital are not in accordance with the anthropometry of the officers, resulting in work discomfort and fatigue. The purpose of this study was to analyze the ergonomics aspects of the storage rack based on the anthropometry of the filling officer. This type of research is descriptive and data collection is done by observation. The population of this study was 5 filing officers. The results of this study indicate that the condition of the storage rack in the filling room of the Airlangga University Hospital is not in accordance of the filling officer. The anthropometry of the filling officer used in designing the rack, namely the reach of the hand up to 202 cm, is used to measure the height of the medical record file storage rack, data fathom length 162 cm is used to reference the length of the medical records file storage rack and shoulder width data used to reference the distance between medical record file storage rack.